2006
DOI: 10.3109/s10165-006-0474-6
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, drinking, sleeping habits, and other lifestyle factors and the risk of systemic lupus erythematosus in Japanese females: findings from the KYSS study

Abstract: Many risk factors have been proposed for systemic lupus erythematosus (SLE). However, there is little information about the relationship between lifestyles and SLE in Japan. Two case control studies were conducted in Kyushu, southern Japan, and in Hokkaido, northern Japan, to examine the relationship between lifestyles and development of SLE in females. The participants were 78 patients and 329 controls in Kyushu and 35 patients and 188 controls in Hokkaido. Smoking was associated with an increased risk of SLE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 9 publications
0
12
0
3
Order By: Relevance
“…However, triggering events for SLE may include many environmental factors 10 . In contrast, another metaanalysis suggested that moderate alcohol consumption (the reference category was nondrinkers) was significantly associated with a decreased risk of SLE (summary OR 0.66, 95% CI 0.49-0.89) based on 5 studies, excluding our preliminary study 11 , where the reference category was subjects who drank less than 1 day per week 12 . In contrast, another metaanalysis suggested that moderate alcohol consumption (the reference category was nondrinkers) was significantly associated with a decreased risk of SLE (summary OR 0.66, 95% CI 0.49-0.89) based on 5 studies, excluding our preliminary study 11 , where the reference category was subjects who drank less than 1 day per week 12 .…”
mentioning
confidence: 73%
“…However, triggering events for SLE may include many environmental factors 10 . In contrast, another metaanalysis suggested that moderate alcohol consumption (the reference category was nondrinkers) was significantly associated with a decreased risk of SLE (summary OR 0.66, 95% CI 0.49-0.89) based on 5 studies, excluding our preliminary study 11 , where the reference category was subjects who drank less than 1 day per week 12 . In contrast, another metaanalysis suggested that moderate alcohol consumption (the reference category was nondrinkers) was significantly associated with a decreased risk of SLE (summary OR 0.66, 95% CI 0.49-0.89) based on 5 studies, excluding our preliminary study 11 , where the reference category was subjects who drank less than 1 day per week 12 .…”
mentioning
confidence: 73%
“…Algumas teorias têm sido formuladas a fim de elucidar a relação entre sexo e LES, entre elas o envolvimento de fatores genéticos, ambientais e hormonais (17,27,48) . De fato, a menarca e a menopausa precoces, além do uso de estrogênio exógeno, estão relacionadas com a suscetibilidade ao desenvolvimento do LES (27) .…”
Section: Figura 1 -Paciente 7: Esfregaço De Borda Lateral De Língua unclassified
“…Alguns estudos sugeriram que o tabagismo poderia representar um fator de risco para o LES (17,18,48) . Em contrapartida, o consumo de bebidas alcoólicas preveniria o desenvolvimento da doença (48) , porém este benefício não foi comprovado em outro estudo (17) .…”
Section: Figura 1 -Paciente 7: Esfregaço De Borda Lateral De Língua unclassified
See 1 more Smart Citation
“…There were no controls with self-reported SLE and with a family history of SLE. Details of the health examination and the self-administered questionnaire have been documented elsewhere (30,31).…”
Section: Significance and Innovationsmentioning
confidence: 99%